Dental Malocclusion and Non-Nutritive Habits: An Epidemiological and Comparative Study - Borja de Melo, Téssia Richelly Nóbrega; Oliveira Araújo, Jamylla Sinnyly de; Monteiro Barros, Géssica de Lourdes; da Silva, Felipe Fialho; Rodrigues, Fernanda Alves (The Journal of Dentists, 2022)
Objective: To study the relationship between dental malocclusions and non-nutritive, and deleterious habits in children from the public school system in a city in the interior of Paraíba, Brazil. Methods: This was a prospective, quantitative and analytical cross-sectional study carried out with 122 children, aged 7 to 11 years, and their caregivers; of both sexes, through the application of a validated questionnaire with the following variables: type of breastfeeding; nutritional, non-nutritive and chewing habits, in addition to intra and extra-oral examination to detect malocclusions and relate them to habits. The data obtained were analyzed by descriptive statistics using the IBM SPSS Statistics Software. Results: The sample, with a mean age of 8.38 years, presented a majority of male (53.3%) and brown participants (56.6%). Of the total, most children were fed mixed, using a cup; did not have allergic rhinitis, adenopathies, snoring or nocturnal drooling; 64.8% did not have non-nutritive habits; and among the chewing habits, onychophagia was the most common (53.3%). Conclusion: There was a significant correlation between non-nutritive habits and the occurrence of malocclusions.